UNIVERSITY INNOVATION COOPERATION WITH BUSINESS COMMUNITY - Tatyana M. Davydenko (Moscow Polytechnic University, 2016)
The article analyzes the trends and mechanisms of interaction between businesses and Voronezh State University. It also presents good practices of implementation of joint projects in the sphere of high-tech industries and in-service training of engineers and technical staff.